Comparing Spatio-Temporal Dynamics of Functional and Taxonomic Diversity of Phytoplankton Community in Tropical Cascading Reservoirs - Resende, Nathália da Silva; Santos, Juliana Barreto Oliveira dos; Josué, Iollanda Ivanov Pereira; Barros, Nathan Oliveira; Cardoso, Simone Jaqueline (Frontiers in Environmental Science, 2022)
Small Hydroelectric Power Plants (SHPs) are considered hydroelectric plants of reduced size and power that modify the landscape in a lower degree. As they are generally built-in sequence along the course of a river, these reservoirs are subject to the Cascading Reservoir Continuum Concept (CRCC), which provides a gradient effect mainly observed on suspended particles and nutrients. These effects can reflect in the phytoplankton community, which respond in terms of changes in their structure and function to environmental changes. Here, we aimed to investigate whether spatial variation would be more explanatory than temporal variation for phytoplankton structure and composition in cascading SHPs reservoirs. Furthermore, we sought to understand the effect of the hydrodynamics of run-of-river and storage reservoirs for phytoplankton community composition. We assessed the predictive power of physical and chemical conditions of the water, and zooplankton density as explanatory variables for phytoplankton taxonomic and functional diversity. The study was carried out over 6 years in three SHPs located on the Paraibuna River, Brazil, totaling 24 campaigns. After counting and identification, the phytoplankton species were classified according to qualitative functional traits related to morphology, physiology, and behavior. The reservoirs had significant differences in nutrients and suspended solids, corroborating with the CRCC. Nonetheless, these variables alone were not able to explain the distribution of phytoplanktonic species. However, as significant coupling between phytoplankton and zooplankton was found, and zooplankton might have influenced the phytoplankton distribution along the longitudinal gradient of the river. Furthermore, changes in taxonomic and functional composition of phytoplankton were mainly related to reservoir hydrodynamics and temporal variation. The last reservoir in the cascade was the one with the greatest phytoplankton species and functional diversity. Taxonomic and functional diversity indices were positively correlated, but at a certain point, functional richness reached a plateau. Here we highlight the complexity of understanding the role of cascading reservoirs in the structure and function of phytoplanktonic communities, which are subject to large spatial and temporal variations, even within the same stretch of a river.